2011
DOI: 10.1177/1741826711423114
|View full text |Cite
|
Sign up to set email alerts
|

Perception of health and understanding of cardiovascular risk among patients with recently diagnosed diabetes and/or metabolic syndrome

Abstract: Patients with recently diagnosed DM and/or with MS have a poor awareness of their CV risk and 42.2% of them think that they have good or excellent health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Seven studies measured the absolute accuracy of risk perceptions , reporting either people's own (eight outcomes) or average (one outcome) perceived absolute risks. One study clearly reported quantitative estimates of the difference between actual and perceived risks , two studies provided enough information (either numerically or graphically ) for us to calculate it, and four studies did not report sufficient quantitative information for an estimate to be derived . Results were mixed, but tended towards overestimation: overestimation (three studies), underestimation (one study) and absence of a significant correlation between actual and perceived risks (meaning that no inference can be made towards under‐ or overestimation; three studies) were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies measured the absolute accuracy of risk perceptions , reporting either people's own (eight outcomes) or average (one outcome) perceived absolute risks. One study clearly reported quantitative estimates of the difference between actual and perceived risks , two studies provided enough information (either numerically or graphically ) for us to calculate it, and four studies did not report sufficient quantitative information for an estimate to be derived . Results were mixed, but tended towards overestimation: overestimation (three studies), underestimation (one study) and absence of a significant correlation between actual and perceived risks (meaning that no inference can be made towards under‐ or overestimation; three studies) were reported.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with other findings that CVD risk is a difficult concept for people to grasp (Angus et al, 2005). In the general population, one study found that 40% of diabetic patients could not estimate their CVD risk, and agreement between risk perception and clinical data was weak (Martell-Claros et al, 2011). Alwan et al (2009) had similar findings, reporting that only half of their participants were able to estimate their perceived risk and the ability to do so was associated with higher socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [5,8] have also shown patient compliance to be the most common barrier to the implementation of cardiovascular risk reduction. A study designed to assess understanding of CV risk by patients recently diagnosed with diabetes mellitus and/or metabolic syndrome treated at primary care centres showed that participants had poor awareness of their CV risk and almost half thought they had good or excellent health [14]. …”
Section: Discussionmentioning
confidence: 99%